Intermediate infrared three-wavelength laser crystal material and preparation method and application thereof
By developing the mid-infrared three-wavelength laser crystal material KDyYGdF10 and growing it using the Bridgman method, the reliability and cost issues of existing mid-infrared lasers have been solved, achieving efficient three-wavelength mid-infrared laser output, which is suitable for fields such as biochemical detection, laser ranging, and optoelectronic countermeasures.
Patent Information
- Application Number
- CN202511339515.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2026-01-16
AI Technical Summary
Existing mid-infrared lasers suffer from poor reliability, complex structure, high price, and some technical indicators fail to meet practical application requirements, especially in terms of laser output in the mid-infrared band.
A mid-infrared three-wavelength laser crystal material, KDyYGdF10, was developed and grown using the Bridgman method. It has low phonon energy, low melting point, and good physicochemical stability. It can generate mid-infrared laser output with three wavelengths of 2849nm, 4235nm, and 4273nm by pumping at 1277nm.
It achieves ultra-wideband absorption and emission performance in the mid-infrared band, enhances the absorption of pump light by the laser crystal, improves the efficiency of mid-infrared laser, and is suitable for generating three-wavelength lasers under Nd:YAG laser pumping.
Smart Images

Figure CN121344774A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a mid-infrared three-wavelength laser crystal material and a preparation method and application thereof, and belongs to the inorganic functional crystal material field. BACKGROUND
[0002] The mid-infrared 2.5-5 mu m band laser is located in the atmospheric infrared window and the molecular fingerprint region, and has important applications in biochemical detection, laser ranging, photoelectric countermeasure and the like. At present, the technical approaches for realizing the mid-infrared laser output mainly include quantum cascade semiconductor lasers and nonlinear optical conversion technologies (including OPO and DFG technologies), but these technologies have defects, so that the corresponding lasers have the defects of poor reliability, complex structure and high price; and some technical indexes (such as output laser power and wavelength tunable range) cannot meet the actual application requirements. The mid-infrared fluoride crystal doped with LD pumped rare earth ions (such as Dy 3+ ) has the advantages of simple structure, high beam quality and the like in realizing the mid-infrared laser, and has irreplaceable advantages in directly amplifying the ns to ps or even fs pulse width high-energy pulse laser at room temperature by breaking through the preparation technology of large-size high-performance mid-infrared laser crystal and optimizing the spectral performance.
[0003] Around the urgent demand of new mid-infrared laser working medium for high-performance laser application at present, the scientific problems of higher phonon energy, easy deliquescence and more mixed crystals generated in the growth process are broken through, a new type of mid-infrared fluoride crystal with good comprehensive performance and excellent quality is found, the crystal growth technology and the spectral performance of rare earth ions in the mid-infrared band are researched, and several high-performance mid-infrared fluoride laser crystals are developed, thereby providing technical support for the construction of practical LD direct pumping type high-energy mid-wave infrared laser. SUMMARY
[0004] The application provides a new type of mid-infrared three-wavelength laser crystal material KDyYGdF 10 The crystal is grown by using the Bridgman method. The laser crystal material is an excellent laser crystal, three ultra-wide band fluorescent emissions in the 2500-4350 nm band are generated by using 1277 nm pumping, the peak wavelengths are 2849 nm, 4235 nm and 4273 nm, and the laser crystal material can be used for generating three-wavelength mid-infrared laser. The laser crystal material has the characteristics of low phonon energy, low melting point, same-component melting and the like, the absorption wavelength is matched with the commercial Nd:YAG laser pumping source, the absorption peak intensity is high, the absorption of the crystal to the pumping light is facilitated, thereby realizing the fluorescent emissions of the peak wavelengths 2849 nm, 4235 nm and 4273 nm in the mid-infrared band, and the laser crystal material is a mid-infrared laser crystal material with great application potential.
[0005] According to a first aspect of the present application, a mid-infrared three-wavelength laser crystal material is provided.
[0006] A mid-infrared three-wavelength laser crystal material, the chemical formula of the mid-infrared three-wavelength laser crystal material is KDyYGdF 10 .
[0007] Optionally, the mid-infrared three-wavelength laser crystal material belongs to cubic system, Fm-3m space group.
[0008] Optionally, the unit cell parameters of the mid-infrared three-wavelength laser crystal material are α = β = γ = 90°,
[0009] Specifically, the unit cell parameters of the mid-infrared three-wavelength laser crystal material are α = β = γ = 90°,
[0010] Optionally, the mid-infrared three-wavelength laser crystal material is in a block shape.
[0011] Specifically, the mid-infrared three-wavelength laser crystal material is in a cylindrical block shape.
[0012] Optionally, the mid-infrared three-wavelength laser crystal material has a size of 10-70mm in at least one dimension.
[0013] Optionally, the mid-infrared three-wavelength laser crystal material has a diameter of 10-20mm and a length of 35-70mm.
[0014] Optionally, the mid-infrared three-wavelength laser crystal material has a diameter of 10mm or 20mm.
[0015] Specifically, the mid-infrared three-wavelength laser crystal material has a size of Φ10mm×50mm.
[0016] Optionally, the mid-infrared three-wavelength laser crystal material has a density of 5.73-5.75g·cm -3 .
[0017] Optionally, in the absorption spectrum of the mid-infrared three-wavelength laser crystal material, there is a broadband absorption peak with a peak wavelength of 1277nm in the wavelength range of 1200-1345nm.
[0018] Optionally, in the fluorescence spectrum of the mid-infrared three-wavelength laser crystal material under 1277nm pumping, the peak wavelength in the wavelength range of 2500-3300nm is 2849nm, and at the same time, there are broadband emission peaks with peak wavelengths of 4235nm and 4273nm in the wavelength range of 4200-4350nm.
[0019] The mid-infrared three-wavelength laser crystal material has good physical and chemical properties, is not hygroscopic in air, has low phonon energy, good physical and chemical stability, and no phase change in air, and has good comprehensive performance.
[0020] According to a second aspect of the present application, a preparation method of a mid-infrared three-wavelength laser crystal material is provided.
[0021] The preparation method of the mid-infrared three-wavelength laser crystal material described above adopts a Bridgman method, and includes the following steps.
[0022] S1, KHF, DyF3, YF3 and GdF3 raw materials are weighed according to stoichiometric ratios, and are filled into a graphite crucible after being fully ground and mixed uniformly, and are compacted;
[0023] S2, the crystal growth furnace is placed, vacuum is drawn, temperature is raised and melted, the graphite crucible is lowered, crystal growth is performed, and the mid-infrared three-wavelength laser crystal material is obtained.
[0024] Optionally, in step S1, the molar ratio of KHF, DyF3, YF3 and GdF3 raw materials is KHF:DyF3:YF3:GdF3=1:1:1:1.
[0025] Optionally, KDyYGdF4 is prepared by weighing, mixing and compacting. 10 A mixing rod.
[0026] Optionally, the KDyYGdF4 has a size of Φ10mm or Φ20mm and a length of 35-70mm. 10 The size of the mixing rod is Φ10mm or Φ20mm, and the length is 35-70mm.
[0027] Optionally, in step S2, the raw materials in the furnace are raised to 1020-1035℃ at a temperature raising rate of 35-75℃ / h; the temperature lowering rate is 1-2℃ / d, the lowering rate of the crucible is 0.7-1.2mm / h, and the lowering lasts for 38-90h before the growth is completed, and then the temperature is lowered to room temperature at a rate of 15-55℃ / h.
[0028] As a preferred embodiment, the preparation method of the mid-infrared three-wavelength laser crystal material includes the following steps.
[0029] S1, KHF, DyF3, YF3 and GdF3 raw materials are weighed according to stoichiometric ratios in a glove box, and are filled into a graphite crucible after being fully ground and mixed uniformly, and are compacted with a polytetrafluoroethylene rod;
[0030] S2, placing into a crystal growth furnace to heat and melt, then slowly lowering the graphite crucible, controlling the temperature gradient, lowering speed of the crucible and temperature lowering procedure in the process, growing the crystal, and obtaining the middle infrared three-wavelength laser crystal material.
[0031] Optionally, the loaded raw materials in the furnace are raised to 1020-1035℃ at a temperature raising rate of 35-75℃ / h, the temperature is slowly adjusted and lowered in the temperature interval, the lowering rate is 1-2℃ / d, the crucible is lowered, the lowering rate is 0.7-1.2mm / h, the lowering lasts for 38-90h, then the growth is ended, and the temperature lowering procedure is controlled, and the temperature is lowered to room temperature at a rate of 15-55℃ / h. During the whole growth period, the furnace is kept in vacuum state, and the vacuum degree is about 0.001Pa.
[0032] As a specific embodiment, the preparation method of the middle infrared three-wavelength laser crystal material at least comprises the following steps:
[0033] KHF, DyF3, YF3 and GdF3 are used as raw materials, the molar ratio of KHF, DyF3, YF3 and GdF3 in the raw materials is KHF:DyF3:YF3:GdF3=1:1:1:1, and the raw materials are weighed and finely ground according to the molar ratio of each chemical substance. After the raw materials KHF, DyF3, YF3 and GdF3 are mixed and compacted in the crucible, they are placed into a crystal growth furnace, vacuumized and heated to 1035℃ for melting, then slowly lowered and lowered the crucible for crystal growth, and the growth conditions are:
[0034] KHF, DyF3, YF3 and GdF3 are used as raw materials, the molar ratio of KHF, DyF3, YF3 and GdF3 in the raw materials is KHF:DyF3:YF3:GdF3=1:1:1:1, and the raw materials are weighed and finely ground according to the molar ratio of each chemical substance. After the raw materials KHF, DyF3, YF3 and GdF3 are mixed and compacted in the crucible, they are placed into a crystal growth furnace, vacuumized and heated to 1035℃ for melting, then slowly lowered and lowered the crucible for crystal growth, and the growth conditions are: 10 The temperature is slowly adjusted and lowered in the temperature interval at a temperature lowering rate of 1-2℃ / d, the crucible is lowered at a lowering rate of 0.7-1.2mm / h, the lowering lasts for 38-90h, then the growth is ended, and the temperature lowering procedure is controlled, and the temperature is lowered to room temperature at a rate of 15-55℃ / h. Before being lowered to room temperature, the furnace is kept in vacuum state, and the vacuum degree is about 0.001Pa. Finally, the cylindrical bulk KDyYGdF4 crystal with a size of diameter 10 or 20mm and length 35-70mm is obtained.
[0035] According to a third aspect of the present application, an application of a middle infrared three-wavelength laser crystal material is provided.
[0036] The application of the above-mentioned middle infrared three-wavelength laser crystal material in middle infrared laser, the middle infrared three-wavelength laser crystal material is used to realize the output of 2849nm, 4235nm and 4273nm three-wavelength laser in the middle infrared waveband of 2300-4500nm under the pumping of Nd:YAG laser.
[0037] The beneficial effects that this application can produce include:
[0038] 1) The laser crystal material KDyYGdF provided in this application 10 It possesses ultra-wideband absorption and emission properties. This laser crystal material can achieve three-wavelength laser output in the mid-infrared bands of 2500-3300nm and 4200-4350nm under 1277nm pump.
[0039] 2) The laser crystal material KDyYGdF provided in this application 10 , compared to ordinary Dy 3+ Compared to fluoride-doped crystals such as CaF2, PbF2, LiYF4, and LuYF4, it has the following advantages: KDyYGdF 10 It exhibits a structure characterized by disordered atomic distribution, with a large absorption cross section and full width at half maximum (FWHM), and an absorption cross section σ at 1277 nm. abs 3.26×10 -21 cm 2 The absorption half-width (FWHM) is 90.1 nm, which is beneficial for the absorption of pump light by the crystal and greatly enhances the fluorescence emission of the crystal in the mid-infrared band. The half-width of the crystal in the mid-infrared fluorescence spectrum reaches more than 240 nm, which is very beneficial for improving the efficiency of mid-infrared laser. Attached Figure Description
[0040] Figure 1 It is the KDyYGdF obtained by the Bridgman method in Example 1. 10 Crystal.
[0041] Figure 2 It is KDyYGdF 10 X-ray powder diffraction pattern of the crystal.
[0042] Figure 3 It is KDyYGdF 10 Room temperature absorption spectrum of crystal.
[0043] Figure 4 It is KDyYGdF 10 Fluorescence spectrum of the crystal in the 2400–3400 nm band under 1277 nm pumping.
[0044] Figure 5 It is KDyYGdF 10 Fluorescence spectrum of the crystal in the 4200–4350 nm band under 1277 nm pumping.
[0045] Figure 6 It is KDyYGdF 10 Dy in crystal 3+ ion 6 H 13 / 2Fluorescence decay curves of energy levels.
[0046] Figure 7 It is KDyYGdF 10 Dy in crystal 3+ ion 6 H 11 / 2 Fluorescence decay curves of energy levels.
[0047] Figure 8 It is KDyYGdF 10 Dy in crystal 3+ Schematic diagram of ion energy level transitions. Detailed Implementation
[0048] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0049] Unless otherwise specified, all raw materials and reagents used in this application are commercially purchased and used directly without processing. The instruments and equipment used adopt the manufacturer's recommended scheme and parameters.
[0050] In the embodiment, the instrument used for crystal growth is a KLS-300 crystal growth furnace, the crucible used is a porous graphite crucible with a diameter of Ф10mm or 20mm, and the raw materials used are KHF, DyF3, YF3 and GdF3 with a purity of 99.9%.
[0051] In the examples, powder X-ray analysis of the samples was performed using a Miniflex 600 powder diffractometer.
[0052] In the examples, the absorption spectra of the samples were measured on a Lambda 950 absorption spectrometer manufactured by Pekin-Elmer; the fluorescence spectra were measured on an FSP 980 fluorescence spectrometer manufactured by Edinburgh Company, UK, with a pump of 1277 nm.
[0053] Example 1 KDyYGdF 10 Preparation of large-size single crystal samples
[0054] The required raw materials are KHF, DyF3, YF3, and GdF3. Prepare the raw materials according to the following chemical reaction formula:
[0055] KHF+DyF3+YF3+GdF3→KDyYGdF 10 +1 / 2H2↑
[0056] According to the above molar ratio of KHF:DyF3:YF3:GdF3 = 1:1:1:1, KHF, DyF3, YF3, and GdF3 were weighed in a glove box, with a total raw material weight of 80g. The raw materials were then finely ground, compacted in a crucible, and placed in a crystal growth furnace. A vacuum was drawn and the temperature was raised to 1035℃ for melting. The temperature was then slowly lowered and the crucible was lowered to allow for crystal growth. The growth conditions were as follows:
[0057] The temperature was increased to 1035℃ at a rate of 50℃ / h. Within this temperature range, the temperature was gradually decreased at a rate of 1.6℃ / day, while the crucible was lowered at a rate of 1.0 mm / h. This lowering process continued for 80 hours until growth was complete. Then, the temperature was controlled to decrease to room temperature at a rate of 35℃ / h. Before reaching room temperature, the furnace was maintained under vacuum, with a vacuum level of approximately 0.001 Pa. The final product was a cylindrical block KDyYGdF with a diameter of 20 mm and a length of 52 mm. 10 Crystals, crystal photographs as follows Figure 1 As shown.
[0058] Crystal structure characterization of the sample in Example 2
[0059] A small piece of transparent crystal was cut from the bulk crystal obtained from the growth process, finely ground into powder, and the structure of the crystal sample was determined using X-ray diffraction.
[0060] The measured diffraction pattern is as follows Figure 2 As shown. Furthermore, the crystal structure was theoretically calculated and analyzed, KDyYGdF 10 It belongs to the cubic crystal system, space group Fm-3m. Its unit cell parameters are... α=β=γ=90°,
[0061] Density was obtained by testing using the following method, the specific steps of which are as follows:
[0062] I. A square crystal with dimensions of 6mm × 6mm × 6mm was cut from Example 1 and its mass was obtained by weighing it using an electronic balance.
[0063] II. Pour an appropriate amount of water into a graduated cylinder and record its volume mark V1. Then, place the square crystal into the graduated cylinder and read the volume mark V2.
[0064] III. Repeat the above steps four times, recording the experimental data each time;
[0065] IV. The density of the crystal was calculated using the formula ρ = m / (V2 - V1). The average value of four experiments was taken, and the density of the crystal was found to be 5.74 g·cm³. -3 .
[0066] Example 3: Spectral performance determination of the sample
[0067] A piece measuring 10.0 × 10.0 × 2.0 mm was cut and processed from the bulk crystal obtained by growth. 3 The crystal slices were then aligned with two parallel planes measuring 10.0 × 10.0 mm. 2 Polishing was performed, followed by detailed spectral performance testing and research.
[0068] The results showed that, Figure 3 As shown, the absorption spectrum of the sample reveals Dy 3+ The characteristic absorption peaks correspond to the ground state energy levels, respectively. 6 H 15 / 2 The transitions to various excited state energy levels (marked in the figure) exhibit a broad absorption peak between 1200-1385 nm, with a peak wavelength of 1277 nm, corresponding to Dy. 3+ : 6 H 15 / 2 arrive 6 H 9 / 2 + 6 F 11 / 2 The transition of KDyYGdF, this absorption band matches the wavelength of the Nd:YAG laser, making KDyYGdF 10 Crystals are well-suited for laser experiments pumped by Nd:YAG lasers.
[0069] Figure 4 and Figure 5 The images show the room-temperature fluorescence spectra of the sample in the 2400–3400 nm and 4200–4350 nm bands, respectively, under a 1277 nm pump. The peak wavelength in the 2500–3300 nm band is 2849 nm, corresponding to Dy. 3+ : 6 H 13 / 2 → 6 H 15 / 2 The transition occurs simultaneously with broadband emission peaks in the 4200–4350 nm band, with peak wavelengths of 4235 nm and 4273 nm, corresponding to Dy. 3+ : 6 H 11 / 2 → 6 H 13 / 2 Leap forward.
[0070] Figure 6 and Figure 7 Samples 6 H 13 / 2 and 6 H 11 / 2 The fluorescence decay curves of the energy levels, after mathematical fitting, yielded fluorescence lifetimes of 871.22 microseconds and 348.79 microseconds for the crystal at the two energy levels, respectively.
[0071] Figure 8 Give the Dy in the sample 3+ A schematic diagram of ion energy level transitions can more clearly and intuitively show the corresponding energy level transitions and energy level lifetimes of the absorption and fluorescence spectra mentioned above.
[0072] Based on the above research and experimental results, KDyYGdF 10 Crystal is a promising laser crystal material that can achieve laser output at three wavelengths in the mid-infrared band: 2849nm, 4235nm, and 4273nm.
[0073] Therefore, the novel crystal KDyYGdF provided by this invention 10 It is an excellent mid-infrared laser gain material.
[0074] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A mid-infrared three-wavelength laser crystal material, characterized in that, The chemical formula of the mid-infrared three-wavelength laser crystal material is KDyYGdF 10 .
2. The mid-infrared three-wavelength laser crystal material of claim 1, wherein, The mid-infrared three-wavelength laser crystal material belongs to a cubic crystal system and has a Fm-3m space group.
3. The mid-infrared three-wavelength laser crystal material of claim 1, wherein, The unit cell parameter of the mid-infrared three-wavelength laser crystal material is α=β=γ=90°, Preferably, the unit cell parameters of the mid-infrared three-wavelength laser crystal material are α = β = γ = 90°, 4. The mid-infrared three-wavelength laser crystal material of claim 1, wherein, The mid-infrared three-wavelength laser crystal material is in a block shape. Preferably, the mid-infrared three-wavelength laser crystal material has a size of 10-70 mm in at least one dimension. Preferably, the mid-infrared three-wavelength laser crystal material has a diameter of 10-20 mm and a length of 35-70 mm.
5. The mid-infrared three-wavelength laser crystal material of claim 1, wherein, The density of the mid-infrared three-wavelength laser crystal material is 5.73-5.75 g·cm -3 .
6. The mid-infrared three-wavelength laser crystal material of claim 1, wherein, The mid-infrared three-wavelength laser crystal material has a broadband absorption peak with a peak wavelength of 1277 nm in an absorption spectrum in a wavelength range of 1200-1345 nm. Preferably, the mid-infrared three-wavelength laser crystal material has a broadband emission peak with a peak wavelength of 4235 nm and 4273 nm in a fluorescence spectrum under 1277 nm pumping in a wavelength range of 4200-4350 nm.
7. The method of producing a mid-infrared three-wavelength laser crystal material according to any one of claims 1 to 6, characterized by, The preparation method adopts a Bridgman method and comprises the following steps: S1, KHF, DyF3, YF3 and GdF3 raw materials are weighed according to a stoichiometric ratio, are fully ground and mixed uniformly, and are then filled into a graphite crucible and are compacted; S2, the filled crucible is placed into a crystal growth furnace, is vacuumized, is heated and melted, is cooled and lowered, and is then subjected to crystal growth to obtain the mid-infrared three-wavelength laser crystal material.
8. The preparation method according to claim 7, characterized in that, In step S1, the molar ratio of the KHF, DyF3, YF3 and GdF3 raw materials is KHF:DyF3:YF3:GdF3=1:1:1:
1.
9. The preparation method according to claim 7, characterized in that, In step S2, the raw materials in the furnace are heated to 1020-1035 ℃ at a heating rate of 35-75 ℃ / h. The cooling rate is 1-2 ℃ / d, the lowering rate of the crucible is 0.7-1.2 mm / h, and the lowering lasts for 38-90 h before the growth is completed, and then the temperature is lowered to room temperature at a rate of 15-55 ℃ / h.
10. Use of the mid-infrared three-wavelength laser crystal material according to any one of claims 1 to 6 in a mid-infrared laser, characterized in that, The mid-infrared three-wavelength laser crystal material is used to realize the output of three-wavelength lasers at 2849 nm, 4235 nm and 4273 nm in a mid-infrared wavelength range of 2300-4500 nm under the pumping of an Nd:YAG laser.